Strengthening Zakat Management in Afghanistan: Lessons from Indonesia and Malaysia Legal Frameworks - Alyusufi, Abdulhaleem Obaid A.; Nukhba, Ghulam Mustafa; Muslimin, JM.; Hidayat, Syahrul Ramadhan (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2024)
This research aims to explore the implementation of zakat management models from Indonesia and Malaysia in Afghanistan to enhance zakat effectiveness. The study employs a comparative analysis of successful practices in both countries, focusing on their applicability to Afghanistan's context. Findings indicate that adopting elements from Indonesia's community participation and Malaysia's centralized approach can improve transparency and efficiency in zakat management. The research concludes that Afghanistan must develop a comprehensive legal framework, establish a national zakat authority, and raise public awareness to overcome existing challenges. By integrating these strategies, Afghanistan can maximize zakat's potential to reduce poverty and promote social justice.Penelitian ini bertujuan untuk mengeksplorasi implementasi model manajemen zakat dari Indonesia dan Malaysia di Afghanistan untuk meningkatkan efektivitas zakat. Studi ini menggunakan analisis komparatif dari praktikpraktik sukses di kedua negara, dengan fokus pada aplikabilitasnya terhadap konteks Afghanistan. Temuan menunjukkan bahwa mengadopsi elemen partisipasi masyarakat dari Indonesia dan pendekatan terpusat dari Malaysia dapat meningkatkan transparansi dan efisiensi dalam manajemen zakat. Penelitian ini menyimpulkan bahwa Afghanistan harus mengembangkan kerangka hukum yang komprehensif, mendirikan otoritas zakat nasional, dan meningkatkan kesadaran masyarakat untuk mengatasi tantangan yang ada. Dengan mengintegrasikan strategi-strategi ini, Afghanistan dapat memaksimalkan potensi zakat untuk mengurangi kemiskinan dan mempromosikan keadilan sosial.